Archaeology and Comics - Barletta, Emiliano; Lo Manto, Alessio (Ex Novo: Journal of Archaeology, 2022)
When considering comics, our initial association tends to be with content tailored for a younger audience. Indeed, within the general publishing industry, the predominant perception aligns comics with a children-oriented paradigm. Nevertheless, over recent decades, comics, particularly in the guise of graphic journalism, have rightfully earned their place as a tool for disseminating information and scientific knowledge. Through a unique fusion of images, artwork, narrative voices, and dialogues, the conventional comic book has transcended mere fantasy storytelling, evolving into a sophisticated form of illustrated reportage. In the forthcoming pages, Emiliano Barletta and Alessio Lo Manto illuminate the vast potential inherent in the language of comic books for communicating scientific archaeology to an adult audience beyond the professional sphere. How might this expressive medium reshape both the perception and substance of our discipline? Can it foster a more inclusive and thus socially relevant dimension within archaeology? Perhaps, as readers of Ex Novo delve into these pages, they will sense our shared viewpoint… Enjoy the read!